Pengetahuan dan Sikap dengan Kepatuhan Penggunaan Alat Pelindung Diri (APD) Petugas Kebersihan - Farjiyanty Latif; Taswin Taswin; Fitriani Fitriani; La Ode Muh.Taufiq (Jurnal Ilmiah Kesehatan Sandi Husada, 2023)
Introduction : According to the International Labor Organization, almost every year there are 1000 times the number of non-fatal work accidents when compared with fatal work accidents. to the income generated by workers. Purpose: This study was to determine the relationship between the level of knowledge and attitudes with the adherence to the use of personal protective equipment (PPE) for cleaners at the Environmental Office of Baubau City. Methods: This research is an analytic research design with a cross sectional study design approach. The population and sample are all cleaning workers who work at the Baubau City Environmental Service, totaling 107 respondents using total sampling. Data collection techniques using a questionnaire, with chi-Square data analysis. Results: research using the chi square test shows that there is a relationship between knowledge (p-value = 0.000 <0.05), and attitude (p-value = 0.000 <0.05) with compliance with the use of personal protective equipment (PPE) for cleaning workers in Baubau City Environmental Service. Conclusion: there is knowledge about compliance with the use of personal protective equipment (PPE) for cleaning staff at the Baubau City Environmental Service. And there is a relationship between attitude and compliance with the use of personal protective equipment (PPE) for cleaning workers at the Baubau City Environmental Service.